Virtual consulting for remote physiotherapy advice in chronic rheumatic diseases during the COVID-19 pandemic - Ilke Coskun Benlidayi (Indian Journal of Rheumatology)
The coronavirus disease-19 pandemic has caused a considerable deterioration in medical practices. This resulted in a rapid shift to telemedicine/telehealth as an alternative to conventional interventions and in-person visits. Telerheumatology practices have been increasing worldwide. Virtual consulting for remote physiotherapy advice in rheumatic diseases is also essential. The present topical review aimed to provide an insight to telehealth for musculoskeletal physiotherapy among patients with rheumatic diseases. Patient assessment, goal setting, teleeducation, and providing individual-based, goal-directed exercises are components of telerehabilitation. Telephone/video calls can be used to further progress the exercise program and to evaluate patient adherence. Future studies on the role of virtual consulting for physiotherapy advice in rheumatic diseases would be of value.